Predicting the Tendency Towards Divorce in Couples Involved in Infidelity Based on Marital Intimacy and Satisfaction with the Mediation of Ethical Orientation Styles - Darbandi, Behjat; Ahadi, Hasan; Khalatbari, Javad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to predict the tendency towards divorce in couples involved in infidelity based on marital intimacy and satisfaction, mediated by ethical orientation styles. Method: The research method was correlational, involving a statistical population of couples seeking counseling in districts one and two of Tehran in 2021. The sample size was 250 individuals of both genders, selected through random quota sampling. Data collection tools included: the Tendency Towards Divorce Scale by Rusbult, Johnson, & Morrow (1986), the Infidelity Scale by Yeni Seri & Kokdemir (2006), the Marital Intimacy Scale by Bagarozzi (2001), the Marital Satisfaction Scale by Enrich (1995), and the Ethical Orientation Styles Scale by Haidt & Graham (2007). Data analysis methods used descriptive statistics, structural equation modeling, and PLS3 SMART software. Findings: The results indicated that there was a negative relationship between marital intimacy and the tendency towards divorce among couples involved in infidelity. There was also a negative relationship between marital satisfaction and the tendency towards divorce in these couples. Marital intimacy and satisfaction could predict the tendency towards divorce mediated by ethical orientation styles. Additionally, there was a significant positive relationship between marital satisfaction and intimacy with ethical orientation styles, with ethical orientation styles mediating the relationship between these variables and the tendency towards divorce. Conclusions: This relationship intensifies when mediated by ethical orientation styles. Thus, with an increase in marital satisfaction, the tendency towards divorce due to infidelity decreases. This justifies the use of interventionist approaches to strengthen marital satisfaction to reduce the tendency towards divorce due to infidelity.